PENGARUH TIGA JENIS PUPUK TERHADAP PERTUMBUHAN MAHONI AFRIKA (Khaya antotheca) - Aditya Hani; Edy Junaidi (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2016)
In social forest management, fertilizer were commonly used to increase productivity and accelerate the harvesting time. Incorrect fertilizer application could decrease the productivity and caused environmental pollution.This study aimed to evaluate the effect of fertilizer on the growth of African mahogany (Khaya anthotheca). This research was used Completely randomized blocked design (CRBD) was used. The Treatments tested were: P0= without fertilizer (a control treatment), P1= chicken manure 5 kg / tree, P2 = goat manure 5 kg/tree, P3= a mixture of chemical fertilizers i.e. a mixture of Urea, TSP, KCl (ratio of 1:2:1 100 g/tree). Each treatment was replicated three times with sixty trees each replication. Total 720 seedling was used in this study. Parameters observed were the chemical properties of soil before and after planting, percentage of survival, growth of high and diameter, and tree canopy width at 2- years old trees. Measurements carried out every 6 months until 2- years old trees. The results showed that the P2 gave the best growth with height = 356 cm, diameter = 5.17 cm and crown wide = 167 cm (P < 0.05).